2005
DOI: 10.1074/jbc.m405065200
|View full text |Cite
|
Sign up to set email alerts
|

Mutant Copper-Zinc Superoxide Dismutase Binds to and Destabilizes Human Low Molecular Weight Neurofilament mRNA

Abstract: The mechanism by which mutated copper-zinc superoxide dismutase (SOD1) causes familial amyotrophic lateral sclerosis is believed to involve an adverse gain of function, independent of the physiological antioxidant enzymatic properties of SOD1. In this study, we have observed that mutant SOD1 (G41S, G85A, and G93A) but not the wild type significantly reduced the stability of the low molecular weight neurofilament mRNA in a dosage-dependent manner. We have also demonstrated that mutant SOD1 but not the wild type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 41 publications
(29 reference statements)
3
35
1
Order By: Relevance
“…The altered mobility shift and the presence of mutant SOD1 in the RNP complex indicate a change in either RBP-VEGF RNA interactions, protein-protein interactions, or both. Strong and colleagues have shown that mutant SOD1 can destabilize low-molecular-weight NFL (neurofilament) mRNA by binding directly to the 3Ј-UTR (Ge et al, 2005). We did not observe direct binding of mutant SOD1 to the VEGF 3Ј-UTR by UV cross-linking.…”
Section: Discussioncontrasting
confidence: 73%
“…The altered mobility shift and the presence of mutant SOD1 in the RNP complex indicate a change in either RBP-VEGF RNA interactions, protein-protein interactions, or both. Strong and colleagues have shown that mutant SOD1 can destabilize low-molecular-weight NFL (neurofilament) mRNA by binding directly to the 3Ј-UTR (Ge et al, 2005). We did not observe direct binding of mutant SOD1 to the VEGF 3Ј-UTR by UV cross-linking.…”
Section: Discussioncontrasting
confidence: 73%
“…A defective neurocytoskeletal network, resulting from unproductive aldolase/NF-mRNA interactions could negatively affect the local concentrations of general translation factors or impair recycling of translational components (Decker and Parker, 1995;Mangus et al, 2003;Amrani et al, 2004). This, in turn, might have effects in trans with deleterious consequences for the normal expression of other gene products (Lin et al, 2004;Ge et al, 2005). The latter becomes critical for large neurons with extraordinary high metabolic demands at specific sites (Wu et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The important substrates for the peroxidase activity include its end product hydrogen peroxide, the SOD protein itself and nucleic acids. However, the conclusion remains elusive as to the direct link between the aberrant properties and the injurious effect of Cu 2 Zn 2 SOD, implying the presence of other toxic pathways [25].…”
Section: Introductionmentioning
confidence: 99%